The influence of culture on accounting judgment – Evidence from Poland and the United Kingdom - Jerzy Gierusz; Katarzyna Kolesnik; Sylwia Silska-Gembka; Anna Zamojska (Cogent Business & Management, 2022)
This study investigates whether national culture influences judgments made by Polish and British accounting professionals when interpreting selected International Financial Reporting Standards (IFRS) that contain uncertainty expressions. We provide evidence from the Central and Eastern European (CEE) region, which is under-investigated in this stream of research. The motivation for this research was provided by the inference that IFRS may not be suitable in Poland because it is a country with significant differences from the profile that best suits application of IFRS. We explicitly test Hofstede-Gray's theoretical framework with respect to conservatism and secrecy values at the individual level. To illustrate core cultural differences (especially in patterns of thinking) between the examined countries, we do not solely rely on the Hofstede theory, but also draw on sociological and historical literature. We do not confirm that national culture, at least based on Hofstede-Gray framework, influences interpretation of uncertainty expressions that require accounting judgment. We find no support neither for Gray's conservatism nor for secrecy hypotheses. This suggests that, in the era of IFRS convergence in the European Union, Hofstede-Gray's framework may have lost its explanatory power in cross-cultural research or is simply not suitable for explaining cultural differences. Additionally, the data analysis reveals that apart from work experience and statutory auditor or chartered accountant qualification, the other personal and professional characteristics of accountants controlled for in our study do not influence their judgments.
Keywords: M41; 650; accounting judgments; culture; conservatism; secrecy; IFRS; interpretations